HISTORY CURRICULUM DEVELOPMENT MODEL TOWARDS NATION BUILDING OF MALAYSIA - Ahmad, Abdul Razaq; Ayudin, Ahmad Rafaai (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
Malaysia is a heterogenic country as the nation is formed by multiracial. Thus, national stability and racial harmony are depending on how relationship among ethnics is enhanced and preserved in order to form a strong nation state. The government is fully aware that educational institutions are the most important disseminators of unity values in enhancing the nation of Malaysia. Schools are the main disseminators through curriculum development and evaluation towards values of unity and national integration, in restoring understanding on the nation and the country. The Curriculum Development Model is the foundation of the research proposal to serve as an implementation manual to inculcate values of unity through History Curriculum. The implementation involves five relevant constructs in defining curriculum, involving comprehensive efforts in providing students education, which are: (1) textual contents (text books) (2) pedagogical elements, (3) inculcation of values, (4) usage of teaching aids and (5) assessment. This research evaluates the relationship among the five constructs towards the elements of racial unity in establsihing the nation state of Malaysia, with the demise of prejudiced and racial gap. The comprehensive curriculum empathizes on the importance of holistic unity components to ensure that the inculcation of values is successfully done through multiple dimensions.